Six vs three months of combined exercise training in patients with chronic obstructive pulmonary disease - Pereira, Ângela Maria (2016)
Communication presented at the 56th ACSM Annual Meeting, May 27-30, 2009. Washington State Convention and Trade Center, Seattle, Washington.